2012
DOI: 10.1021/ac301119r
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance Graphene-Titania Platform for Detection of Phosphopeptides in Cancer Cells

Abstract: Phosphopeptides play a crucial role in many biological processes and constitute some of the most powerful biomarkers in disease detection. However they are often present in very low concentration, which makes their detection highly challenging. Here, we demonstrate the use of a solution-dispersible graphene-titania platform for the selective extraction of phosphopeptides from peptide mixtures. This is followed by direct analysis by surface-enhanced laser desorption/ionization time-of-flight mass spectrometry (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 52 publications
0
39
0
Order By: Relevance
“…The detailed methods used for LC-MS/MS were described previously (26). Briefly, separation of the iTRAQ-labeled peptides was carried out on an Eksigent nanoLC Ultra and ChiPLC-nanoflex (Eksigent, Dublin, CA) in the "Trap Elute" configuration.…”
Section: Protein Identification and Quantificationnano-lc Electrospramentioning
confidence: 99%
“…The detailed methods used for LC-MS/MS were described previously (26). Briefly, separation of the iTRAQ-labeled peptides was carried out on an Eksigent nanoLC Ultra and ChiPLC-nanoflex (Eksigent, Dublin, CA) in the "Trap Elute" configuration.…”
Section: Protein Identification and Quantificationnano-lc Electrospramentioning
confidence: 99%
“…(e) Selective extraction and direct detection of phosphopeptides using graphene (G)-TiO 2 platform. {Reprinted with permission from [122]. ©2012 American Chemical Society}.…”
Section: Discussionmentioning
confidence: 99%
“…Loh's group developed a G-titania (G-TiO 2 ) platform for selective extraction of phosphopeptides from cancer cells [122]. These functionalized platforms were selectively conjugated with phosphopeptides, thereby increasing and expanding the library of phosphopeptides in cancer cells, which is useful in profiling disease-related signaling pathways.…”
Section: Nanomaterials-based Maldi-ms For Bacterial Identification Anmentioning
confidence: 99%
“…Hybridization with other nanomaterials to obtain better selectivity for specific analytes (e.g., with TiO 2 for phosphopeptides [97][98][99][100] Yan et al [120] reported an IMAC (immobilized metal ion affinity chromatography) material with polydopamine coated on the surface of graphene and functionalized with titanium ions (Ti 4+ -G@PD) as an immobilized metal ion affinity chromatography platform for phosphoproteome followed by MALDI-TOF MS. In this approach, the application of the Ti …”
Section: Graphenementioning
confidence: 99%